A single exercise test for assessing physiological and performance parameters in elite rowers: The 2-in-1 test - Bourdon, P. C.; David, A. Z.; Buckley, J. D. (Journal of Science and Medicine in Sport, 2009)
Testing to determine blood lactate thresholds for prescription of rowing training is usually conducted separately from performance testing (i.e. 2000 m time trial). The purpose of this study was to investigate whether the testing required to determine blood lactate thresholds and performance in elite rowers could be reduced by undertaking a single test combining incremental exercise with a 2000 m time trial. Ten elite rowers (age 20.9 ± 2.1 years, mean ± S.D.) performed, on separate occasions and in random order, an incremental seven-step rowing test (INCR), a 2000 m time trial (2k), or a combined test involving the performance of six incremental submaximal workloads followed by 15 min of recovery and then a 2000 m time trial (2-in-1). Physiological and performance parameters (blood lactate thresholds, accumulated oxygen deficit, heart rate, work parameters) determined during 2-in-1 were not significantly different from those determined during INCR or 2k, except for peak oxygen uptake which was higher during 2-in-1 compared with INCR (4.23 ± 0.22 versus 4.14 ± 0.20 l min-1, p = 0.02), and peak rating of perceived exertion which was lower during 2-in-1 compared with INCR (19.4 ± 0.2 versus 19.9 ± 0.1, p = 0.02). We conclude that physiological and performance parameters that have traditionally been assessed during separate incremental exercise and 2000 m time trial testing in elite rowers can be validly determined during a single combined exercise test.